On oscillation theorems for differential polynomials - Belaidi, Benharrat; ElFarissi, Abdallah (Electronic Journal of Qualitative Theory of Differential Equations, 2009)
In this paper, we investigate the relationship between small functions and differential polynomials gf (z) = d2f 00 + d1f 0 + d0f, where d0 (z), d1 (z), d2 (z) are meromorphic functions that are not all equal to zero with finite order generated by solutions of the second order linear differential equation f 00 + Af0 + Bf = F, where A, B, F 6≡ 0 are finite order meromorphic functions having only finitely many poles.
Keywords: Linear differential equations; meromorphic solutions; order of growth; Exponent of convergence of zeros; Exponent of convergence of distinct zeros; Differential polynomials